Synthesis, in vitro and in vivo evaluation of 2-aryl-4H-chromene and 3-aryl-1H-benzo[f]chromene derivatives as novel α-glucosidase inhibitors. Issue 1 (1st January 2019) - Spasov, Alexander A.; Babkov, Denis A.; Osipov, Dmitry V.; Klochkov, Vladlen G.; Prilepskaya, Diana R.; Demidov, Maxim R.; Osyanin, Vitaly A.; Klimochkin, Yuri N.
Graphical abstract: Highlights: Series of novel 2-aryl-4 H -chromene and 3-aryl-1 H -benzo[ f ]chromenes were synthesized. Four compounds were identified as potent α-glucosidase inhibitors. Structure-activity relationships were derived via molecular modeling. Lead compound6a is superior to acarbose with IC50 of 62.26 µM. Lead compound6a effectively prevents postprandial hyperglycemia in rats. Abstract: Herein we report a study of novel arylchromene derivatives as analogs of naturally occurring flavonoids with prominent α-glucosidase inhibitory properties. Novel inhibitors were identified via simple stepwise in silico screening, efficient synthesis, and biological evaluation. It is shown that 2-aryl-4H-chromene core retains pharmacophore properties while being readily available synthetically. A lead compound identified through screening inhibits yeast α-glucosidase with IC50 of 62.26 µM and prevents postprandial hyperglycemia in rats at 2.2 mg/kg dose.